Viral-induced neuroinflammation: Different mechanisms converging to similar exacerbated glial responses - Rocamonde, Brenda; Hasan, Uzma; Mathieu, Cyrille; Dutartre, Hélène (Frontiers in Neuroscience, 2023)
There is increasing evidence that viral infections are the source/origin of various types of encephalitis, encephalomyelitis, and other neurological and cognitive disorders. While the involvement of certain viruses, such as the Nipah virus and measles virus is known, the mechanisms of neural invasion and the factors that trigger intense immune reactions are not fully understood. Based on recent publications, this review discusses the role of the immune response, interactions between viruses and glial cells, and cytokine mediators in the development of inflammatory diseases in the central nervous system. It also highlights the significant gaps in knowledge regarding these mechanisms.